PENGARUH EKSTRAKURIKULER DAN MOTIVASI BERPRESTASI TERHADAP KEPERCAYAAN DIRI - Zulkarnaen . (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2005)
The aims of this stiiiiy is to find out the effect of extracurricular outbound activity and basket hall to the level of self confidence for the student In SLTP Negeri 2 Bekasi. The aims of this study also to the find out the effect of achievement motivation both outbound and basket ball activity, and also aimed to find out the differences between achievement motivation both high and low achievement motivation. The analysis was applied experimental method and factorial analysis 2 X 2 by simple random sampling with 52 students as sample. The instrument for this is self confidence test and an achievement motivation test with tested questionnaire. And there is effect between extracurriadar outbound and extracurricidar basket ball activity.